THE DIFFERENCES OF MAXIMUM BLINK INTERVAL IN HYPERTENSION PATIENTS WITH AND WITHOUT DRY EYE DISEASE: Oral Presentation - Observational Study - Resident - I NYOMAN CAHYA SETIABUDI; I Gusti Ayu Made Juliari; Cokorda Intro Dewiyani Pemayun (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Hypertension and the use of antihypertensive drugs are thought to be one of the risk factors for dry eye disease due to a decrease in tear production. Maximum blink interval (MBI), which is the time during which the eye can remain unblinking, can be an easy method for assessing dry eye disease because local conditions in the eye can affect blinking patterns. This study aims to determine the difference in the average MBI in hypertensive patients with dry eye disease and hypertensive patients without dry eye disease. Methods : This study is a cross-sectional analytic study which was conducted in January 2022-June 2022. The sample of the study was hypertensive patients with dry eye disease and without dry eye disease who were treated at the Internal Medicine Polyclinic, Kidney-Hypertension Division at Sanglah Hospital (Prof I.G.N.G. Ngoerah Hospital). The sample selection technique was consecutive sampling and the total sample in the study was 81 people. Data were collected using the OSDI questionnaire and TBUT and Schirmer examinations to assess dry eye disease, blood pressure tests to assess hypertension, and MBI examination. Results : The results showed that the average MBI in hypertensive patients with dry eye disease twice shorter than in hypertensive patients without dry eye disease (p<0.001). Conclusion : This shows that MBI can be used as a modality for screening and screening for dry eye disease in hypertensive patients. MBI can be an alternative for practitioners to objectively assess dry eye disease in primary health care where there is no complete ophthalmological facility.